STUDI PEMANFAATAN GAS BUANG KNALPOT (FLUE GAS) SEBAGAI DELIMING AGENT ALTERNATIF PADA PENGOLAHAN KULIT KAMBING - Prasetyo Hermawan; Alfani Risman Nugroho (Politeknik ATK Yogyakarta, 2020)
ABSTRACT The purpose of this research was to study the process of removing lime from the skin by flowing flue gas into a solution of lime in a reactor consisting of an absorption reactor and a deliming reactor. CO2 gas which is part of the flue gas will react with the Ca(OH)2 suspension so that the pH of the lime liquid and the pH of the skin will decrease and in this study three types of motorbikes are used as a source of flue gas. The results showed that flue gas flowing in lime solution for 30 minutes resulted in a relatively constant pH of lime. The exhaust gas from motor 2 (flow rate of 6.4 liters / minute) which is flowed in the reactor has been able to reduce the pH of the lime solution from 12.60 to 7.77 (decreased by 4.49 pH units). The use of CO2 can only reduce the pH of water from 8.14 to 7.57 (decreased by 0.57 pH units). In the implementation of the variation in the height of the absorption column, the optimal value for the column height is 100 cm and is able to reduce the pH of water from 12.26 to 7.14 (decrease by 5.12 pH units). In the experiment, the addition of skin in a stirred reactor caused the ability to decrease the pH of the liquid and skin to be reduced, the pH of the lime solution was still 8.33 in the first 30 minutes and the pH stability only occurred at 45 minutes. The character of the deliming skin was also compared with the deliming method using (NH4)2SO4